Сравнительная оценка эффективности активных методов детоксикации у новорожденных - Межирова, Н.М.; Данилова, В.В.; Овчаренко, С.С.; Штыкер, С.Ю. (Актуальні проблеми транспортної медицини, 2010)
У статті викладені результати порівняльної оцінки ефективності різних методів активної детоксикації, які були застосовані для лікування синдрому ендогенної інтоксикації у новонароджених. Вживані методи детоксикації підвищують загальну резистентність організму до дії високої концентрації «середніх» молекул. Порівняльна оцінка еферентних методів детоксикації по кінетиці «середніх» молекул і концентраційним порогам основних клінічних симптомів показала перевагу використання сорбційної детоксикації у поєднанні з УФО аутокрови, а наступним поефективності є плазмаферез. In the article the results of comparative evaluation of the efficacy of different methods of active detoxication, which were applied for the complex treatment of endogenous intoxication syndrome in one half of affected newborns, are adduced. The obtained data testify to the effect that any efferent method increases general resistance of an organism to the influence of high concentrations of average weight molecular peptides. Comparative assessment of efferent methods of detoxication grounded on kinetics of average weight molecular peptides showed an advantage of the use of sorption detoxication in comparison with ultraviolet irradiation of autoblood and plasmapheresis.